Interactive Articulate Storyline Food Chain Edugame to Improve Fifth-Grade Students Critical Thinking Skills - Toni Agus Ardie; Iin Purnamasari; Joko Siswanto (Jurnal Penelitian Pendidikan IPA, 2026)
Developing an effective game-based learning environment to improve elementary students' critical thinking skills remains a challenge in science education, particularly for food chain learning. This study aimed to develop and evaluate an Interactive Articulate Storyline-based Food Chain Edugame using a Research and Development (R&D) approach with the ADDIE model. Product quality was evaluated through expert validation, teacher and student practicality assessments, instrument testing, and effectiveness analysis using a quasi-experimental pretest–posttest control group design. The critical thinking instrument consisted of 12 essay items, of which 10 were valid and demonstrated high reliability (Cronbach's Alpha = 0.877). The developed learning environment met the criteria for validity, practicality, and effectiveness. No significant difference was found between the experimental and control groups in the pretest (p = 0.725), whereas the posttest showed a significant difference (p < 0.001). The experimental group achieved a higher mean posttest score (85.63) and normalized gain (0.680) than the control group (67.34; 0.273). These findings demonstrate that integrating game-based learning activities, formative assessment, and immediate feedback within a meaningful learning design effectively enhances elementary students' critical thinking skills.